Hypermethylated CDO1 and CELF4 in cytological specimens as triage strategy biomarkers in endometrial malignant lesions - Qi, Bingli; Sun, Ye; Lv, Yaohua; Hu, Pei; Ma, Yanli; Gao, Wenying; Li, Shumei; Zhang, Xin; Jin, Xitong; Liou, Yuligh; Liu, Pei; Liu, Shikai (Frontiers in Oncology, 2023)
Objective Developing a noninvasive and reliable triage test for endometrial malignant lesions is an important goal, as it could help to reduce the number of invasive diagnostic procedures required and improve patient survival. We aimed to estimate the diagnostic value of DNA methylation levels in cervical cytological samples of endometrial cancer (EC) and endometrial atypical hyperplasia (AH).A total of 607 women who had indications for endometrial biopsy in the Department of Obstetrics and Gynecology of Cangzhou Central Hospital from October 2022 to April 2023 were enrolled in this study. The cervical exfoliated cells were collected for gene methylation before endometrial biopsy. Clinical information, tumor biomarkers, and endometrial thickness (ET) of transvaginal ultrasonography (TVS) were also collected. With endometrial histopathology as the gold standard, multivariate unconditional logistic regression was applied to analyze the risk factors of endometrial malignant lesions. The role of cysteine dioxygenase type 1 (CDO1) and CUGBP Elav-like family member 4 (CELF4) gene methylation as a triage strategy biomarker in endometrial malignant lesions was specifically explored. 2 Results Multivariate logistic regression analysis showed that premenopausal ET ≥ 11 mm or postmenopausal ET≥5 mm, CDO1 ΔCt ≤8.4 or CELF4 ΔCt≤8.8 were the risk factors for AH and EC, with ORs (95%CI) of 5.03(1 .83-13.82) and 6.92 (1.10-43.44), respectively (P values<0.05). The sensitivity and specificity of CDO1/CELF4 dual gene methylation assay for AH and EC reached 84.9% (95%CI: 75.3%-94.5%) and 86.6% (95%CI: 83.8%-89.5%), respectively. ET combined with DNA methylation detection further improved the specificity to (94.9%, 95%CI: 93.1%-96.8%).The accuracy of cervical cytology DNA methylation is superior to other clinical indicators in the non-invasive examination of endometrial malignant lesions. DNA methylation combined with TVS can further improve the specificity, and can as a promising biomarker triage strategy in women with suspected endometrial lesions.